Meganema claviformis , Fraser 1939 - Calder, Dale R.; Choong, Henry H. C. (Zenodo, 2018)
Meganema claviformis Fraser, 1939b Lafoeina maxima Levinsen, 1893: 182, pl. 6, figs. 9–12. Keratosum complexum Hargitt, 1909: 379, figs. 8–10. Levinsenia maxima .— Hadži, 1917: 55. Eupoma maximum .— Stechow, 1920: 45. Meganema claviformis Fraser, 1939b: 60, figs. 2a–c. Lafoeina claviformis .— Fraser, 1947a: 240. Keratosum maximum .—Calder, 1991: 10. Syntypes. BCPM 976-00302-001: Canada, Nunavut, Dolphin and Union Strait, off Cape Bexley, 68°59’N, 115°40’W, 16 m, summer 1936 or 1937, RCMP Vessel St. Roch, dredge, two colony fragments, coll. Sgt. H.A. Larsen; slide. Lectotype, by present designation. RBCM 976-00302-001: Canada, Nunavut, Dolphin and Union Strait, off Cape Bexley, 68°59’N, 115°40’W, 16 m, summer 1936 or 1937, RCMP Vessel St. Roch, dredge, one colony fragment (specimen on the left side of the slide BCPM 976-00302-001), 8 mm high, in only fair condition, without gonophores, coll. Sgt. H.A. Larsen; slide. Paralectotype. BCPM 976-00302-001: Canada, Nunavut, Dolphin and Union Strait, off Cape Bexley, 68°59’N, 115°40’W, 16 m, summer 1936 or 1937, RCMP Vessel St. Roch, dredge, one colony fragment, 8 mm high, in only fair condition, without gonophores, coll. Sgt. H.A. Larsen; slide. Type locality. Canada, Nunavut: Dolphin and Union Strait, off Cape Bexley, 68°59’N, 115°40’W, 16 m (Fraser 1939b). Current status. Invalid. Remarks. In describing Meganema claviformis , Fraser (1939b) reported that the hydroid was “attached to sponges, barnacle shells, etc.” No name-bearing type was designated by him. The only type material of the species in existence is mounted on a slide (BCPM 976-00302-001) in the Fraser Hydroid Collection at the RBCM. Two specimens occur on the slide, both of them fragmentary. While the fragments may be part of a single colony, we have not assumed so for nomenclatural purposes (ICZN Recommendation 73F). The specimen on the left side of the slide has been designated here as the lectotype (RBCM 976-00302-002) to objectively define the species and ensure stability of nomenclature. The specimen ...